Changes in adipokine concentrations in antidepressant-resistant bipolar depression after ketamine infusion and electroconvulsive therapy. (21st April 2023) - Dmitrzak-Weglarz, Monika; Tyszkiewicz-Nwafor, Marta; Rybakowski, Filip; Permoda-Pachuta, Agnieszka
Abstract: Objectives: This study attempts to assess the concentration of two opposite-acting adipokines (anti-inflammatory adiponectin and pro-inflammatory resistin) in antidepressant-resistant patients undergoing ketamine infusion (KI) and electroconvulsive therapy (ECT). Methods: The study group comprised 52 patients hospitalised due to episodes of depression in the course of bipolar disorders. The Hamilton depression scale was used to assess the intensity of the depression symptoms before starting therapy and one day after its completion. The serum concentration of adipokines was determined before and after the therapeutic intervention using an ELISA method. Results: Baseline adipokine levels differed between patients receiving KI and ECT therapy. Regardless of the procedure used, these levels changed after treatment, with the nature of these changes being different. In the case of KI, the adiponectin levels increased, and resistin levels decreased. In contrast, after ECT, the concentrations of both adipokines decreased. Changes in adipokine concentrations correlated with improvement in mental status, as assessed by the Hamilton Rating Scale, type of bipolar disorder, and gender. Conclusions: Adipokines remain interesting candidate biomarkers in assessing the state and course of the disease depending on the therapeutic procedure applied. However, the relatively small study group and limited original research available for discussion justify further investigation.